ANALISIS YURIDIS PERJANJIAN KONSTRUKSI JALAN ANTARA PT.MUTIARA ACEH LESTARI DENGAN DINAS BINA MARGA DAN CIPTA KARYA BERDASARKAN (STUDI PUTUSAN PENGADILAN BANDA ACEH NOMOR 46/PDT.G/2013/PN-BNA) - ANNA FAHRENI (PREMISE LAW JURNAL, 2016)
Road construction agreement between PT. Mutiara Aceh Lestari with Dinas Bina Marga dan Cipta Karya Aceh, arising due to natural disasters, landslides in December 2010. This type thesis research using normative juridical research, by examining the statutory provisions and regulations in the procurement of goods / services, Legal No. 18 OF 1999 President No. 4 of 2015, and Government Regulation No. 21 Year 2008. From the research, carried out in their execution of work before the contract was made because of a natural disaster is not contrary to law. The agreement form of default in road construction between PT. The default form in the contract of road construction among PT. Mutiara Aceh Lestari and Dinas Bina Marga and Cipta Karya was in which the debtor had good performance, yet it was not in accordance with or committed an errorAceh province District Court Consideration No. 46 / Pdt. G / 2013 / PN-BNA was granted as part of a lawsuit of PT. Mutiara Aceh Lestari because the identity is not clear from the PT. Mutiara Aceh Lestari, precisely because of the PT. Mutiara Aceh Lestari does not violate the Law No. 40 of 2004